Investigating the molecular mechanisms of mutant C9orf72 human iPSC-derived astrocyte-mediated motor neuron deficits - Stavrou, Maria (The University of Edinburgh, 2024)
Amyotrophic Lateral Sclerosis (ALS) is a progressive, incurable, and invariably fatal neurodegenerative condition characterized by the loss of motor neurons (MNs). In addition, cellular abnormalities in ALS have long been known not to be restricted to MNs. Over the last two decades, multiple lines of evidence from pathology, genetics, and experimental systems implicate a central role for non-neuronal cells, particularly astrocytes, in ALS pathogenesis. This is not surprising given the intimate structural and functional associations of astrocytes with, inter alia, the synapse and vasculature. The finding that sporadic and familial ALS are largely phenotypically and pathologically indistinguishable highlights the value of studying familial ALS to gain mechanistic insight into this condition. The intronic hexanucleotide repeat expansion (G4C2) in the C9orf72 gene is the most common cause of inherited ALS and accounts for approximately 10% of sporadic ALS cases. Studies to date have largely focused on the consequences of C9orf72 in MNs. In comparison, the cell-autonomous and non-cell-autonomous consequences of C9orf72 in astrocytes are comparatively understudied, and the underpinning molecular mechanisms remain largely unexplored. One powerful strategy to interrogate the role of astrocytes in ALS is to harness genetic discoveries through human induced pluripotent stem cells (hiPSCs) and gene editing technologies. The generation of paired gene-edited controls, where the only variable is the mutation of interest, allows causality to be assigned to any given phenotype. Against this background, during my PhD, I used multiple independent patient-derived induced pluripotent stem cell (iPSC) astrocytes and MNs harboring the C9orf72 mutation, along with paired gene-corrected controls, and undertook a series of studies to investigate (1) astrocyte-mediated contact-dependent mechanisms through mixed-species RNA-Seq to determine transcriptional dysregulation in wildtype primary rodent MNs induced by cocultured C9orf72 astrocytes, and (2) astrocyte-mediated non-contact-dependent mechanisms by performing transcriptomic and proteomic analyses on MNs treated with astrocyte-conditioned medium (ACM), as well as a comprehensive profiling of ACM by mass spectrometry. Importantly, the present study uncovers a previously unreported mechanism of axonal transport that relies on astrocyte-neuronal interaction. Although disrupted axonal transport, altered mitochondrial bioenergetics, and astrocyte dyshomeostasis have been implicated in the aetiopathology of ALS, the role of astrocytes in regulating axonal transport and neuronal bioenergetic status is unknown. Here, it is shown that the astrocyte genotype directly regulates axonal transport. Specifically, in coculture, (i) C9-mutant astrocytes induce axonal transport deficits in control MNs, and (ii) control astrocytes reverse the axonal deficits found in monocultures of C9-mutant MNs. Moreover, this work demonstrates cell-autonomous and non-cell-autonomous effects of C9-mutant astrocytes on mitochondrial bioenergetic function. Finally, selective genetically mediated boosting of mitochondrial bioenergetic activity in C9-mutant astrocytes rescues the astrocyte-mediated axonal transport deficits observed in coculture with control or C9-mutant MNs. Collectively, these data suggest a novel role for astrocytes in regulating axonal transport, which is mediated through astrocyte-neuronal metabolic crosstalk, providing evidence for astrocyte metabolism as a potential therapeutic target for ALS.
Keywords: Amyotrophic Lateral Sclerosis; ALS; neurons; glia; astrocytes; ALS astrocytes; mitochondria repair; C9orf72 gene; C9-mutant astrocytes